KETERKAITAN ANTARA PROGRAM PENDIDIKAN KEWIRAUSAHAAN, KEPUASAN PERILAKU INOVASI, DAN KEPUASAN KINERJA - Evin Elvino (Riset Manajemen dan Akuntansi, 2017)
This study investigates and analyzes the influence of Entrepreneurship Education Programme (EEP) on Satisfaction with Performance (SWP) and Satisfaction with Innovation Behaviour (SWIB) as mediation variable. 104 batik Entrepreneurs in Surakarta (Laweyan and Kauman) that has already run the buisness for 1 year, are used as samples. Non-probability and purposive sampling are used as Sampling method and technique. The data Analysis acquired by using Structural Equation Modeling (SEM) results are: 1) Entrepreneuship Education Programme (EEP) influences on satisfaction with innovation behaviour (SWIB); 2) Entrepreneuship Education Programme (EEP) influences on satisfaction with performance (SWP); 3) Satifaction with innovation behaviour influences on satisfaction with performance; 4) Satisfaction with innovation behaviour mediated the influence of Entrepreneuship Education Programme (EEP) on satisfaction with performance. Keywords: Entrepreneurship Education Programme, satisfaction with innovation behaviour, satisfaction with performance